Epidemiology of Traumatic Spinal Cord Injuries in Iran; a Systematic Review and Meta-Analysis - Saheban Maleki, Mohsen; Khedri, Behzad; Ebrahimpour Roodposhti, Maryam; Askari Majdabadi, Hesamedin; Seyedrezaei, Seyedeh Omolbanin; Amanat, Nasir; Poursadeqiyan, Mohsen; Khajehnasiri, Farahnaz; Amiri, Roya (Archives of Academic Emergency Medicine, 2022)
Introduction: Understanding the epidemiology of traumatic spinal cord injuries (TSCIs) can be helpful for policymakers and planners to consider appropriate strategies to control and prevent these injuries. This study aimed to determine the epidemiological characteristics of TSCI in Iran in order to increase knowledge and awareness of these injuries. Methods: A systematic literature search was conducted up to January 2022 in the electronic databases, including PubMed, Scopus, Web of Science, Google Scholar, SID, Iranmedex, and Magiran. The quality of included studies was evaluated using the STORBE checklist. Comprehensive meta-analysis was used to analyze the data. Results: Nineteen studies involving 9416 cases were included in the study. Participants’ pooled mean age was 35.80 ± 1.07 years (95% CI: 33.69 to 37.91), of whom 69% (95% CI: 68% to 70%; P<0.05) were male. The most frequent TSCI occurred in the age group of less than 30 years. Motor vehicle collisions (MVCs) was the most common cause of TSCI (57%; 95% CI: 25% to 63%), followed by falls (32%; 95% CI: 26% to 38%). Most participants had thoracolumbar (27%; 95% CI: 10% to 55%) and cervical injuries (23%; 95% CI: 16% to 31%), respectively. The incidence of TSCI was estimated at 10.5 per million people. The prevalence of TSCI was 3 per 10000 people. The mortality rate due to TSCI was 3.9% (95% CI: 0.02 to 0.06; P<0.05). Conclusion: Based on the findings of this meta-analysis, the pooled incidence and prevalence of TSCI in the Iranian population were 10.5/1000.000 people and 4.4/10.000 people, respectively. TSCIs had occurred more frequently in males following MVCs, and in the age group under 30 years. The pooled mortality rate due to TSCI was 3.9% (95% CI: 0.02 to 0.06; P<0.05).